48. ASSESSMENT OF THE FLUCTUATION OF ANTI-SARS – COV-2 IGG TITLE AND RELATED FACTORS IN COVID- 19 PATIENTS (Vietnam Journal of Community Medicine, 2025)
Objective: To determine the change in anti-SARS-CoV-2 IgG concentration in CoVid-19 patients in Hanoi and to study the factors related to anti-SARS-CoV-2 IgG concentration in the above subjects.Subjects and methods: Cross-sectional descriptive study at 4 time points: T0 (While being treated at the Central Tropical Hospital: 271 patients); T6 (After 6 months of infection: 250 patients); T12 (After 12 months of infection: 250 patients) and T18 (After 18 months of infection: 270 patients).Results: Regarding age: group T0 has the highest average age: 55.5±16.4 (4 - 90); In terms of gender: women account for the majority in groups T6; T12 and T18, while men in group T0 are more numerous, accounting for 59.4%. BMI of the 4 stages are similar, mainly classified as normal (18 - 25); In terms of underlying diseases: Group T0 has the highest rate of underlying diseases, accounting for 60.89%, while T6 is 25.2%; group T12 is 22%; group T18 is 21.9%; In terms of vaccination history: Group T0 has received the least 32.1% of vaccinations; In terms of disease severity: Group T0 has the highest rate of severe and critical: 43.5% and 28.8%. Antibody concentration of group T0: 494.55 UI/ml (106.43- 1119.17); T6: 355.58 UI/ml(241.95- 507.13); T12: 173.62 UI/ml (133.01- 229.47); T18: 74.9 UI/ml (53.13- 106.17).Conclusion: Correlation was found between disease types and anti-SARS CoV-2 antibody concentration in group T0. Anti-SARS CoV-2 antibody concentration decreased over time but still existed up to 18 months after infection.
Keywords: Covid-19; anti-SARS CoV-2 IgG; disease types; Son Tay General Hospital